Control interno en la Ferreteria “Tecniglass” del cantón Babahoyo periodo 2021. - Rodríguez Rodríguez, Tairis Ysabel (2022)
The development of this Research Project includes the Internal Control developed in the Province of Los Ríos, Babahoyo Canton, which is dedicated to the purchase and sale of hardware products in general. The present investigation was carried out with the purpose of carrying out internal control in one of the most important items of the company, such as INVENTORY. Likewise, the level of profitability of the mentioned item was presented. For the process, research methods were applied such as inductive, deductive, based mainly on exploratory research, being instruments used for observation, as well as data collection through internal control questionnaires to administrative staff and interviews with company directors. applied the COSO I model to Internal Control procedures and in accordance with legal provisions. Finally, an Internal Control Report was presented according to the results obtained, in which the findings are detailed, pointing out the pertinent conclusions, which will allow the company to make appropriate decisions, since these standards allow it to comply with the objectives and goals set, as well as well as the company will be able to make optimal decisions. The result of this work included the evaluation of internal control through 10 questions. This places the company at a LOW control risk level of 84.40%. and a LOW Confidence Level of 15.5%, as shown by the evaluation of internal control based on the COSO I model. Finally, there are the Annexes, in which the execution of the Investigation work carried out in the TECNIGLASS Company is observed and verified.